2020
DOI: 10.1038/s41467-020-18878-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into assembly of the ribosomal nascent polypeptide exit tunnel

Abstract: The nascent polypeptide exit tunnel (NPET) is a major functional center of 60S ribosomal subunits. However, little is known about how the NPET is constructed during ribosome assembly. We utilized molecular genetics, biochemistry, and cryo-electron microscopy (cryo-EM) to investigate the functions of two NPET-associated proteins, ribosomal protein uL4 and assembly factor Nog1, in NPET assembly. Structures of mutant pre-ribosomes lacking the tunnel domain of uL4 reveal a misassembled NPET, including an aberrantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 63 publications
5
34
0
Order By: Relevance
“…As expected, shutting down the GAL1/10 promoter in glucose containing medium prevented growth of the three conditional r-protein expression mutants, while all four strains could be cultivated in galactose containing medium ( S2 Appendix ) [ 21 , 38 ]. Consistent with previous studies, some growth delay was observed in galactose containing medium in the strains expressing the Nog1-TAP fusion protein ( S2 Appendix , compare the colony size of the untagged with the one of tagged strains in YPG) [ 34 , 39 ]. LSU particles associated with TAP tagged Nog1 were affinity purified after four hours shift to glucose containing medium.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As expected, shutting down the GAL1/10 promoter in glucose containing medium prevented growth of the three conditional r-protein expression mutants, while all four strains could be cultivated in galactose containing medium ( S2 Appendix ) [ 21 , 38 ]. Consistent with previous studies, some growth delay was observed in galactose containing medium in the strains expressing the Nog1-TAP fusion protein ( S2 Appendix , compare the colony size of the untagged with the one of tagged strains in YPG) [ 34 , 39 ]. LSU particles associated with TAP tagged Nog1 were affinity purified after four hours shift to glucose containing medium.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, corresponding densities could not be detected in Nog1-TAP associated LSU populations. The observed effects on growth rate by TAP tagging of Nog1 (see above, S2 Appendix ) and previous LSU folding analyses of particles from Nog1 mutant strains [ 34 ] thus suggest that progression of downstream nuclear LSU maturation steps was delayed in this situation to some extent.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, Arabidopsis 60S subunit seems to be closer related to the human 60S regarding the high density of modifications. In human ribosomes, helix 74 is important for the accurate structure of the nascent polypeptide exit tunnel (NPET) (Wilson et al, 2020) and helix 93 is a contact site for hydroxylated uL2, which induces structural rearrangements in the PTC of the mature ribosomes (Yanshina et al, 2015). The same could hold true for plants as well.…”
Section: A View On the Modifications In Arabidopsis 25s Rrnamentioning
confidence: 99%
“…PET assembly occurs much earlier in the nucleolus when pre-ribosomal particles are slowly processed and crafted [46]. Thus, disrupting PET assembly in the early biogenesis steps might cause a debilitated tunnel structure [47] and cause the need for a dedicated proof reading step catalyzed by REIL later on in the cytoplasm. After testing this example, we propose that plant ribosome heterogeneity is non-random and is likely controlled by specialized mechanisms during biogenesis that preferentially assemble groups of RPs or RP paralogs in a concerted process.…”
Section: Introductionmentioning
confidence: 99%